"Play It Again, Billy, but This Time with More Mistakes": Divergent Improvisation Activities for the Jazz Ensemble. (March 2014) - Healy, Daniel J.
The jazz ensemble represents an important performance opportunity in many school music programs. Due to the cultural history of jazz as an improvisatory art form, school jazz ensemble directors must address methods of teaching improvisation concepts to young students. Progress has been made in the field of prescribed improvisation activities and materials that use scales, arpeggios, and chord changes as bases for learning concepts. However, less effort has been devoted to creative improvisation, such as experimentation, personal discovery, and listening. This article describes benefits of devoting teaching time to such concepts and outlines three easy warm-ups: melodic variation, free improvisation, and limited-note exercises, all of which can be taught to young jazz ensembles along with harmonic and theory-based methods.